Alcohol septal ablation for hypertrophic obstructive cardiomyopathy and bilateral lung transplantation for idiopathic pulmonary fibrosis: a case report - Puchnerova, Veronika; Bonaventura, Jiri; Lischke, Robert; Veselka, Josef (European heart journal. Case reports, 2023)
BACKGROUND: We present an uncommon case of a patient with hypertrophic obstructive cardiomyopathy and idiopathic pulmonary fibrosis. The case demonstrates the importance of pre-transplant cardiology workup and the need of interdisciplinary approach in diagnosing the cause of dyspnoea. CASE SUMMARY: The 52-year-old male patient was diagnosed with idiopathic pulmonary fibrosis in 2019 and gradually became oxygen dependent due to progression of dyspnoea. Bilateral lung transplantation was recommended in 2021. During pre-transplant cardiology workup, the patient was diagnosed with hypertrophic cardiomyopathy with left ventricular outflow tract (LVOT) obstruction. Considering the high surgical risk of the patient, alcohol septal ablation was performed with subsequent decrease of LVOT gradient. Bilateral lung transplantation was successfully performed afterwards. The patient's symptoms improved to NYHA class II at one year follow-up. DISCUSSION: We present a rare case of combined cause of dyspnoea-coexistence of hypertrophic obstructive cardiomyopathy and idiopathic pulmonary fibrosis in one patient. Due to high surgical risk, the patient underwent alcohol septal ablation with successful elimination of LVOT gradient and subsequently bilateral lung transplantation.
Keywords: Hypertrophic obstructive cardiomyopathy; Alcohol septal ablation; Case report; Idiopathic pulmonary fibrosis; Lung transplantation